2002
DOI: 10.1034/j.1399-3046.2002.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant basiliximab with low‐dose calcineurin inhibitors in children post‐liver transplantation

Abstract: Orthotopic liver transplantation (OLT) is effective therapy for end-stage liver disease but immunosuppression with calcineurin inhibitors (CNI) leads to significant nephrotoxicity, resulting in either a reduction of dosage to below the therapeutic level or omission of the drug altogether. Basiliximab (Bx) is a human/mouse chimeric monoclonal antibody that inhibits binding of interleukin-2 (IL-2) to IL-2 receptors and thus prevents proliferation of T cells, which is the main step in the development of acute cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Single-center studies suggest that renal function is stable for most pediatric LT recipients 1 to 5 years after transplantation [169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] and that only a small subgroup develops progressive deterioration. In a recent multicenter, cross-sectional study of the measured GFR in 397 pediatric patients 1 or more years (mean 5 5.2 years) after LT, 17.6% had a measured GFR < 90 mL/ minute/1.73 m 2 .…”
Section: Prevalence and Riskmentioning
confidence: 99%
“…Single-center studies suggest that renal function is stable for most pediatric LT recipients 1 to 5 years after transplantation [169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] and that only a small subgroup develops progressive deterioration. In a recent multicenter, cross-sectional study of the measured GFR in 397 pediatric patients 1 or more years (mean 5 5.2 years) after LT, 17.6% had a measured GFR < 90 mL/ minute/1.73 m 2 .…”
Section: Prevalence and Riskmentioning
confidence: 99%
“…A multicenter adult study comparing daclizumab induction, mycophenolate mofetil, corticosteroids, and delayed reduced‐dose tacrolimus with a standard‐dose tacrolimus and corticosteroids schedule reported less nephrotoxicity with equal efficacy in acute rejection incidence, as well as graft and patient survival 75. A similar study was also done in the pediatric patient population with similar results 76…”
Section: Immunosuppressive Medications and Their Complicationsmentioning
confidence: 72%
“…47,48 The most common cause of ESRD after OLT is CNI-induced nephrotoxicity (75%) followed by progression of underlying renal disease (11%), hepato-renal syndrome (7%), and focal sclerosing glomerulosclerosis (7%). 49 The impact of CNIs on renal function and the fact that early kidney dysfunction is a predictor of late chronic renal failure after OLT, 50 have led to a number of studies exploring the use of antibody induction to delay or minimize CNI exposure [51][52][53][54][55][56] In a prospective, open-label, nonrandomized study using basiliximab induction followed by delayed initiation (median delay 36 hours) and reduced dose (trough level of 5 to 10 ng/mL) of Tac with maintenance MMF and steroid taper, Lin et al 54 demonstrated a "renal-sparing" effect of basiliximab induction in adult living donor OLT. They reported a significantly lower incidence of renal insufficiency at the third post-OLT month in the basiliximab group compared to the control (no induction) group (26% vs 67%) with similar incidence of ACR, CMV infection, and new-onset diabetes mellitus.…”
Section: Specific Uses Of Basiliximab In Liver Transplantationmentioning
confidence: 99%